RE: Contribution of Fecal Calprotectin and Fecal Immunochemical Tests to the Evaluation of Patients with Ulcerative Colitis - Hu, Tingpeng; Zhang, Zhimei; Song, Fusheng; Zhang, Wenguang; Yang, Jun (Turkish Journal of Gastroenterology, 2024)
Cite this article as: Hu T, Zhang Z, Song F, Zhang W, Yang J. RE: Contribution of fecal calprotectin and fecal immunochemical tests to the evaluation of patients with ulcerative colitis. Turk J Gastroenterol. 2024;35(6):511.